Beyond hearing aid fitting: Investigating the feasibility of providing tele-rehabilitation for adult hearing aid users in a South African public health context - Khatib, Nuha (Department of Health and Rehabilitation Sciences, 2022)
Introduction: Disabling hearing loss is one of the most common sensory deficits; affecting approximately 466 million people worldwide. In the South African context, public health facilities have an uneven ratio between audiologists and patients in need and thus audiological services are often minimal. Successful application of tele-health may increase the scope of audiological services for hearing aid (HA) users. Research is needed to investigate feasibility of tele-health for audiological rehabilitation programmes such as auditory training (AT). Aim and Objectives: This study aimed to investigate the feasibility of implementing a telerehabilitation programme in a South African public health context. Objectives included: 1) determining online AT compliance; 2) determining the effect of online AT on speech perception in noise; 3) assessing experience and benefit of tele-rehabilitation through questionnaires and interviewing; and 4) cost estimation around tele-rehabilitation implementation. Research Design: A convergent mixed methods design with a feasibility approach was utilized. Data collection was through questionnaires, in-booth speech assessments, online AT and face-to-face interviewing. Participants undertook online AT over four weeks. Pre-/post- online AT: the APHAB, QuickSIN, Entrance/Exit Questionnaires, Interviews and System Usability Scale were administered. Descriptive statistics were used to analyse the quantitative data collected, and descriptive thematic analysis was used for the qualitative data. Study sample: Purposive sampling was used and three female adult (35 - 55 years) HA users from a public health facility participated. Results: 1) High compliance rate (84.82%) with 3 hours 25 minutes total clinician contact time, 2) clinical benefit with improvement in listening skills and perceived HA benefit, 3) positive participant feedback, and 4) estimated cost at R1350.00 per person. Conclusions: Findings from this feasibility study can be seen as positive indicators towards the use of tele-health as a delivery modality for audiological rehabilitation, also a tele-health hybrid model is recommended. However, larger-scaled research is needed.